Labor Migration, EU Enlargement, and the Great Recession 2016
DOI: 10.1007/978-3-662-45320-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Did Post-enlargement Labor Mobility Help the EU to Adjust During the Great Recession? The Case of Slovakia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Indeed, the growing presence of Eastern European and third country migrants has strongly mitigated the demand for Southern EU migrants over the years. As suggested by the available data, Central and Eastern European migrants occupy mostly low-and mid-skilled labour positions primarily in low value-added economic sectors (Kahanec and Kurekova 2014 ). Nonetheless, it should also be noted that in the post-enlargement period, the share of EU10 migrants with high educational attainment residing in the EU15 has increased substantially (Kahanec 2013 ).…”
Section: Past and Current South-north Flows: Why History Is Not Repeamentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the growing presence of Eastern European and third country migrants has strongly mitigated the demand for Southern EU migrants over the years. As suggested by the available data, Central and Eastern European migrants occupy mostly low-and mid-skilled labour positions primarily in low value-added economic sectors (Kahanec and Kurekova 2014 ). Nonetheless, it should also be noted that in the post-enlargement period, the share of EU10 migrants with high educational attainment residing in the EU15 has increased substantially (Kahanec 2013 ).…”
Section: Past and Current South-north Flows: Why History Is Not Repeamentioning
confidence: 98%
“…The linkages between the state of the European economies and migration have emerged as one of the most important topics in recent scientifi c debates on migration (Canetta et al 2014 ;Castles and Vezzoli 2009 ;. A growing number of publications have assessed the dynamics of the crisis and its impacts on the mobility patterns of EU nationals as well as of third country nationals (see Kahanec and Kurekova 2014 ;OECD 2011OECD , 2012Kaczmarczyk and Stanek 2015 ). What needs to be emphasized is that although in its initial phase, the economic deterioration spread throughout most of the developed countries, its consequences are not equally distributed among Member States (Kahanec and Zimmermann 2014 ).…”
Section: The Economic Crisis In Eu Countries: An Overviewmentioning
confidence: 99%
“…Studies have shown that immigrants are more concentrated in the states that offer generous benefits and, as a result, the degree of participation to welfare systems are more sensible to changes in these benefits compared to the national population (Borjas, 1999a;Josifidis et al, 2014;Fuest & Thum, 1999). When conditions change unfavorably for migrants, the migration flows redirect to countries with greater opportunities on the labour market and more generous social protection systems (Kahanec & Kurekova, 2014).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Labour mobility is an important adjustment mechanism in the European Union labour market (Kahanec & Kurekova, 2014). Individuals have many reasons to migrate.…”
Section: Immigration Process In European Unionmentioning
confidence: 99%
“…The question of selectivity to return is of major importance in the context of the wage assimilation of returnees. A number of empirical studies, including Kahanec and Zimmermann (2010), Pungas, Toomet, Tammaru, and Anniste (2012), Kahanec and Kureková (2014), and White (2014) have been devoted to the analysis of selection to return patterns and their interrelation with post-return integration outcomes.…”
Section: Empirical Strategymentioning
confidence: 99%